Turbulence in the tropical stratosphere, equatorial Kelvin waves, and the quasi-biennial oscillation - Rachel Atlas; Aurélien Podglajen; Richard Wilson; Albert Hertzog; Riwal Plougonven (Proceedings of the National Academy of Sciences, 2025)
The tropical stratosphere is the gateway to the global stratosphere and a commonly proposed location for solar geoengineering. The dynamics of this remote and difficult to observe region are poorly understood, particularly at turbulent length scales. Existing observational estimates of turbulence frequency and strength vary widely. Furthermore, the sources of turbulence and the relationship between turbulence and the mean flow are largely unknown. We assembled a 21-y database of high vertical resolution (10 m) radiosonde data from four equatorial sites in two ocean basins to study tropical stratospheric turbulence frequency, variability, and sources. Turbulent layers thicker than 200 m are identified using subcritical Richardson number as a proxy for turbulence. We show that the turbulent fraction of the tropical stratosphere is strongly modulated by the quasi-biennial oscillation (QBO). Turbulence is enhanced during the QBO phase shifts, and the atmosphere is most turbulent right before the QBO phase switches from negative to positive, where turbulent instabilities typically occur within specific phases of Kelvin waves. Turbulence is less common when the QBO phase is well established, and the atmosphere is least turbulent during the negative phase of the QBO. The turbulent fraction of the equatorial lower stratosphere varies over a factor of ten depending on QBO phase. This relationship provides a robust observational constraint on the multiscale dynamics within this region, which is useful for evaluating atmospheric models, studying wave-mean flow interactions in the context of the QBO, and informing the operation of stratospheric aircraft and the injection of aerosol for geoengineering.